Black River Cemetery: An anthropological study of the human remains exhumed from a historic Cape Town burial ground - Pütter, Christie (Department of Human Biology, 2021)
The Black River Cemetery, located in modern day Athlone (a suburb of Cape Town), was open for burials from 1867 - 1951, serving three Anglican Churches. The recent (2017) excavation of the historic site allowed for the analysis of the exhumed skeletal remains. The outcome of the skeletal analysis is valuable as the lives documented on the skeleton of a past group of people can write the story of individuals and communities that may have otherwise been omitted from the history books. The aim of this study is to describe demography, lifestyle and disease for a group of people living at the Cape between the 18th and early 20th centuries. The excavation of the cemetery yielded 1,305 graves of which 1,050 contained skeletal remains. Skeletal preservation was varied due to taphonomic influences, but overall it was poor with high fragmentation and taphonomic loss of skeletal material. The skeletal analysis performed utilised several well-established methodologies used in bioarchaeological and forensic anthropological disciplines and produced a body of information encompassing the demographics for this historic skeletal sample. Historical research on the Colonial Cape, coupled with the Black River Cemetery history and burial registers was employed to provide the context to the results of the skeletal analysis. The historic research suggests that the community and people buried there were most likely hardworking people of the poorer communities at the Cape in the 18th and 19th century with a division of labour between men and women. In the period of time that the cemetery was receiving burials, multiple social, political and economic changes occurred including; the bubonic (black) plague, Spanish influenza epidemic, the Boer War, the First World War and the Diamond Rush. It also saw the beginnings of racially segregated living and forced relocations. This backdrop provides an interesting landscape on which to view the skeletal analysis. The data analyses showed that the mortality profiles were skewed from the normal profiles determined by Weiss (1973). The sex ratio was skewed toward males indicating a greater mortality risk for men while the age mortality profiles showed a higher child and juvenile mortality and lower old adult mortality than is typically expected in a cemetery assemblage. This is an indicator of the effects of the epidemics and other factors reducing survivability of individuals. The low frequencies of periosteal reactions also may point to the poor survival capability as individuals may have succumbed to infections before the effect would be exhibited on the skeletal material. Pathological and stress indicators also show a sexually dimorphic trend with males exhibiting greater frequencies of degenerative joint disease, fractures, osteophytic growths and rates of dental attrition. Stature analysis showed a sexually homogenous group of people suggesting a lower health status and likely malnourishment or undernutrition. The social environment in which people lived likely contributed to a weakened immune system, and the generally poor health status of the people. The experience of the people living in Black River and the surrounding areas appears to be one of hard, repetitive labour and nutritional stress within an everchanging urban setting.